COVID-19 Shock and Global Value Chains: Is There a Substitute for China?. Issue 15 (7th December 2020) - Qin, Meng; Liu, Xiuyan; Zhou, Xiaoxue
ABSTRACT: COVID-19 has had a worldwide impact. The consensus is that the sudden pause of global production and the shrinking international trade will contract the global economy. This study explores the short-term impact of the COVID-19 shock on global value chains (GVC), especially considering China's production-capacity damage. Findings suggest that downstream countries and sectors suffer more from China's production disruption than upstream ones. The Most impacted countries are the United States, South Korea, Japan, and Germany; while the most-affected sectors include electronic and optical equipment, textiles, machinery, manufacturing, and wholesale trade. It is found that China is too important in GVC to be substituted for in the current world economy.